Dasymaschalon bachmaensis (Annonaceae), a new species from Bạch Mã National Park, North Central Coast region, Vietnam - Ðỗ, Ngọc-Ðài; Lý, Ngọc-Sâm; Lê, Thị-Hương; Vương, Trương Bá (Phytotaxa, 2018)
A new species of Dasymaschalon (Annonaceae), D. bachmaensis, from Bạch Mã NP, Thừa Thiên-Huế Province from North Central Coast region, Vietnam, is described and illustrated here. It shares several characteristics with D. glaucum, D. sootepense and D. wallichii (the leaves are glaucous, the petals are somewhat ovate and spirally twisted when mature, the stamen connectives are truncate and glabrous, the ovaries are hairy, and the stigmas are glabrous) but differs from them in having an obtuse leaf base, larger triangular-ovate sepals that are hairy on both surfaces, pale greenish-yellow petals, fewer stamens, smaller fruits that are not constricted between seeds, and smaller subglobose seeds. Details on distribution, ecology, phenology preliminary conservation assessment of D. bachmaensis, a key to Dasymaschalon species in Vietnam and a distribution map are provided.